Neurological regeneration - Pham, Phuc Van (Springer, 2017)
This invaluable resource explores the regenerative potential of stem cells in the nervous system, with a focus on clinical applications. The expertly authored chapters discuss cell-based therapies for spinal cord injury and regeneration, traumatic brain injury, glioblastoma, Parkinson's Disease, ischemic stroke, cell banking, human embryonic stem cells and related concerns, harvesting of adipose tissue, and more. These topics are contextualized within a discussion of future directions of these therapies. Neurological Regeneration, part of Springer´s Stem Cells in Clinical Applications series, is essential reading for scientists, researchers, advanced students and clinicians working in stem cells, neurology, regenerative medicine or tissue engineering.- Resumé vydavatele
Includes index.
Keywords: biomedicínské inženýrství; neurologie; kmenové buňky; nemoci nervového systému; regenerační medicína; transplantace; biomedical engineering; neurology; stem cells; nervous system diseases; regenerative medicine; transplantation; elektronické knihy; sborníky; electronic books; papers of several authors